(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2023)
There has been an increase in awareness among Malaysians about settlement through the court. If there is a dispute that occurs in their daily life and it fails to be rightly resolved, the place they will go to is definitely the court. As a result, court cases are gradually increasing to the point where they have to be postponed or delayed to another date. When such things occur, it indirectly gives a bad or negative image to the judicial institution in Malaysia. Therefore, to prevent this matter from getting out of control, the court judge will suggest the parties involved to mediate at the Court Mediation Centre that is run by the High Court. Although this Centre has long been established in Malaysia, most Malaysians still do not know about its existence. Therefore, the main objective of this study is to inform the public about this Centre and to assess the role and challenges of this Centre in resolving disputes. This study used library research, that is, legal provisions, court cases, textbooks, journal articles, newspapers, conference proceedings and seminar papers. Structured interview was also conducted with court officers or appointed mediators. The findings from this study show that the Court Mediation Centre is actually effective in resolving disputes, especially family disputes. Therefore, the variety of efforts need to be intensified so that all the challenges in the Court Mediation Centre can be effectively overcome, in addition to increasing public awareness of the existence of the Centre. Keywords: High Court, Court Mediation Centre, caucus, order, mediation, conflict Full text: PDF